COVID-19 vaccination and pregnancy-induced hypertension risk in women undergoing assisted reproduction: reproductive epidemiology - Ma, Shujuan; Zheng, Yixiang; Fang, Mingli; Xiong, Yiquan; Hu, Liang; Liu, Yvonne; Gong, Fei; Krämer, Bernhard; Lin, Ge; Hocher, Berthold (Human reproduction, 2025)
Does COVID-19 vaccination affect the risk of pregnancy-induced hypertension (PIH) in women undergoing ARTs, and does this risk differ based on vaccine type (inactivated vs recombinant) and timing relative to embryo transfer?Women who received inactivated COVID-19 vaccines before undergoing ART had a significantly increased risk of developing PIH, particularly when vaccinated with two or more doses or when embryo transfer occurred within 1 month of vaccination.COVID-19 vaccination during pregnancy reduces the risk of severe COVID-19 illness with no significant safety concerns for the mother or fetus. PIH is a common complication in ART pregnancies, particularly in older women and those with higher BMI, but the effects of different COVID-19 vaccine types on PIH risk in ART pregnancies remain unclear.A retrospective cohort study analyzing 3911 women undergoing ART after receiving COVID-19 vaccines. The study period spanned from 1 December 2020 to 30 September 2022.Participants were categorized based on COVID-19 vaccination status, vaccine type (inactivated vs recombinant), and the timing of vaccination relative to embryo transfer. The primary outcome was the development of PIH. Multivariate robust Poisson regression was used to assess the association between vaccination and PIH, while subgroup analyses explored the risk across variables like age, BMI, and embryo transfer type.Women vaccinated with an inactivated COVID-19 vaccine prior to embryo transfer had a significantly higher incidence of PIH compared to unvaccinated counterparts (relative risk [RR] = 1.45; 95% CI 1.10-1.92; P = 0.009). In contrast, recombinant vaccines did not show a significant association with increased PIH risk (RR = 1.19; 95% CI 0.69-2.05; P = 0.537). The risk was particularly pronounced among women receiving two or more doses of the inactivated vaccines and those who had embryo transfers within 1 month of vaccination. Subgroup analyses showed elevated PIH risk in women aged ≥30 years old, those with BMI ≥22 kg/m2, individuals with secondary infertility, and those undergoing cleavage-stage or fresh embryo transfers.The study’s retrospective design limits causal inference. The sample is from a single ethnic background, and familial hypertension history was not available, potentially introducing residual confounding.The study suggests that the type and timing of COVID-19 vaccination may influence PIH risk in ART pregnancies. These findings underscore the need for careful consideration of vaccination type and timing in ART protocols and highlight the importance of further prospective studies to validate these results before influencing clinical decision-making.This work was supported by the Hunan High-Level Talent Aggregation Project [2022RC4007]; the National Natural Science Foundation of China [72004148]; the Hunan Provincial Enterprise Joint Fund [2024JJ9093]; the Hunan Provincial Grant for Innovative Province Construction [2019SK4012]; the Deutschlandstipendium of the Charite; the non-restricted research grant of Boehringer Ingelheim Ltd.; and the Research Grant of CITIC-Xiangya [YNXM-202304, 202217]. The authors report no conflicts of interest.N/A.
Online veröffentlicht: 11. April 2025
Gesehen am 12.06.2025